A Simpler Proof of Cohen's Factorization Theorem. Issue 5 (28th May 2019) - Mortini, Raymond
Abstract: We present a simpler proof than the original of P. J. Cohen's factorization theorems for nonunital Banach algebras with an approximate identity.